Emerging applications of superhydrophilic-superhydrophobic micropatterns - Ueda, Erica; Levkin, Pavel (Advanced materials, 2013)
Water on superhydrophilic surfaces spreads or is absorbed very quickly, and exhibits water contact angles close to zero. We encounter superhydrophilic materials in our daily life (e.g., paper, sponges, textiles) and they are also ubiquitous in nature (e.g., plant and tree leaves, Nepenthes pitcher plant). On the other hand, water on completely non-wettable, superhydrophobic surfaces forms spherical droplets and rolls off the surface easily. One of the most well-known examples of a superhydrophobic surface is the lotus leaf. Creating novel superhydrophobic surfaces has led to exciting new properties such as complete water repellency, self-cleaning, separation of oil and water, and antibiofouling. However, combining these two extreme states of superhydrophilicity and superhydrophobicity on the same surface in precise two-dimensional micropatterns opens exciting new functionalities and possibilities in a wide variety of applications from cell, droplet, and hydrogel microarrays for screening to surface tension confined microchannels for separation and diagnostic devices. In this Progress Report, we briefly describe the methods for fabricating superhydrophilic-superhydrophobic patterns and highlight some of the newer and emerging applications of these patterned substrates that are currently being explored. We also give an outlook on current and future applications that would benefit from using such superhydrophilic-superhydrophobic micropatterns.
Gesehen am 17.02.2022